HEDONIC, EUDONIC AND MAKARISTIC HAPPINESS: DIALOGUE BETWEEN ANCIENT PHILOSOPHY AND POSITIVE PSYCHOLOGY - de Sousa, Ágabo Borges (Seven Editora, 2024)
This work proposes to raise a discussion about the concepts of happiness in Positive Psychology from the understandings of happiness in ancient philosophy, considering Cyrenaic hedonism, Aristotelian eudaimony, Nicomachean Ethics and Epicurus’ Makaristics. Presenting the three philosophical concepts, it is understood that the Makaristic understanding of happiness has been neglected in Positive Psychology, and can be included in the psychological construct to enrich the proposal of happiness. DOI: https://doi.org/10.56238/sevened2024.037-102